Heterobimetallic iridiumIII-europiumIII complex: the role of donor energy on sensitising the EuIII ion - Canisares, Felipe da Silva Manrique [UNESP]; Silva, Renan Caike [UNESP]; Davolos, Marian Rosaly [UNESP]; Pires, Ana Maria [UNESP]; Lima, Sergio Antonio Marques [UNESP] (Royal Society of Chemistry (RSC), 2023)
In luminescent devices, the combination of red, green, and blue luminophores (RGB system) allows the creation of other colours in the electromagnetic spectrum, including the perception of white light. Among the three fundamental colours necessary to create the RGB system, normally, the red colour has received great attention compared with the others because red luminophores present lower Φ due to the energy gap law. Red emitters are easily obtained using EuIII ion, however, although the red emitters based on the EuIII ion have high colour purity, the Φ normally is lower compared with red emitters based on the IrIII ion, even though the colour purity of the latter is not so high. Thus, to produce efficient red-emitting complexes, a strategy that has been developed is the synthesis of heterobimetallic d-f complexes to join the high Φ of the d-metal complexes with the high colour purity of the EuIII ion. Herein, a novel dual bimetallic emitter was synthesised and fully characterised, the [{Ir(dfppy)2(μ-bpdc)}3Eu2]Cl3·nH2O·mCH3OH (dfppy is the 2-(2,4-difluorophenyl)pyridine cyclometallating ligand, and the ancillary ligand bpdc is the 2,2′bipyridine-3,3′-dicarboxylic acid). This complex was immobilised in a polymeric PMMA film presenting a high Φ value, 42.2 ± 4.2%, in the yellow spectral region. Its precursor, the novel green-emitting IrIII complex, [Ir(dfppy)2(bpdc)], showed 97.2 ± 9.7% of Φ after doped in PMMA matrix. Both films were used to coat a UV-LED chip to investigate the photophysical properties when these complexes are applied to create phosphor-converted LEDs. The bimetallic prototype exhibited higher radiant photostability after 18 h of operation compared with the heteroleptic IrIII complex-doped film. For the first time, the lowest triplet energy (19 103 cm−1) from an IrIII complex that efficiently sensitises the EuIII ion in an IrIII-EuIII heterobimetallic complex has been determined using voltage modulation in a UV-coated LED prototype, which can be used to engineer new pure red-emitting d-f bimetallic systems.